FIRE FIGHTING SIMULATION USING GAME MACHINE OPEN SOURCE - Wardijono, Bheta Agus (Universitas Gunadarma, 2009)
This paper explains the development of fire fighting simulation system using open source software. The objective of the development is to help user in the process of fire fighting in case of fire inside the building, by making the best use of computer-based graphic visualization and simulation technologies. Delta3D is a game machine which has been chosen and is required for developing this simulation (game simulation) with the open source as consideration.Keyword(s): Open source, Simulation, Fire Fighting, Game Simulation, Game Machine, Delta3D.Subject Description : I.6.Simulation and Modeling | I.6.8.Types of Simulation | Gaming